2014
DOI: 10.4236/ojgen.2014.45038
|View full text |Cite
|
Sign up to set email alerts
|

Association between rs1800795 (-174 G/C) Polymorphism in the Promoter of <i>IL</i>6 Gene and Risk of Relapsing-Remitting Multiple Sclerosis (RRMS) in Isfahan Population

Abstract: Multiple sclerosis (MS) is an inflammatory demyelinating disease of central nervous system (CNS) that mostly affects young adults. The etiology of MS includes both genetic and environmental factors. A single nucleotide polymorphism (SNP) linked with autoimmune disorders predisposition, identified by Genome-Wide Association Study (GWAS) among genes which immunologically related are considerably over signified. The goal of the current study is investigation of the association between rs1800795 (-174 G/C) polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Additionally, other studies discovered a link between the CC genotype and the C allele of the IL-6 G174C SNP and the onset of cardiovascular events, establishing it as a risk factor for myocardial infarction [64,65]. In contrast, previous research has shown that the IL-6 G174C SNP is not associated with an increased risk of cardiovascular disease in Tunisians [66], Chinese [67], or the Isfahan population [68].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies discovered a link between the CC genotype and the C allele of the IL-6 G174C SNP and the onset of cardiovascular events, establishing it as a risk factor for myocardial infarction [64,65]. In contrast, previous research has shown that the IL-6 G174C SNP is not associated with an increased risk of cardiovascular disease in Tunisians [66], Chinese [67], or the Isfahan population [68].…”
Section: Discussionmentioning
confidence: 99%